Toxoplasma gondii infection in workers occupationally exposed to unwashed raw fruits and vegetables: a case control seroprevalence study - Alvarado-Esquivel Cosme; Estrada-Martínez Sergio; Liesenfeld Oliver (Parasites & Vectors, 2011)
Abstract Background Through a case control seroprevalence study, we sought to determine the association of Toxoplasma gondii infection with occupational exposure to unwashed raw fruits and vegetables. Methods Subjects, numbering 200, who worked growing or selling fruits and vegetables, and 400 control subjects matched by age, gender, and residence were examined by enzyme immunoassays for the presence of anti-Toxoplasma IgG and IgM antibodies. Socio-demographic, clinical, and behavioral characteristics from the study subjects were obtained. Results Of the 200 fruit and vegetable workers, 15 (7.5%) of whom, and 31 (7.8%) of the 400 controls were positive for anti-Toxoplasma IgG antibodies (P = 0.96). Anti-Toxoplasma IgM antibodies were found in 2 (1%) of the fruit workers and in 11 (2.8%) of the control subjects (P = 0.23). Seroprevalence of Toxoplasma antibodies increased with age (P = 0.0004). In addition, seropositivity to Toxoplasma was associated with ill status (P = 0.04), chronic tonsillitis (P = 0.03), and reflex impairment (P = 0.03). Multivariate analysis showed that Toxoplasma infection was associated with consumption of raw meat (OR = 5.77; 95% CI: 1.15-28.79; P = 0.03), unwashed raw fruits (OR = 2.50; 95% CI: 1.11-5.63; P = 0.02), and living in a house with soil floors (OR = 3.10; 95% CI: 1.22-7.88; P = 0.01), whereas Toxoplasma infection was negatively associated with traveling abroad (OR = 0.28; 95% CI: 0.12-0.67; P = 0.005). Conclusions This is the first report of seroprevalence and contributing factors for Toxoplasma infection in workers occupationally exposed to unwashed raw fruits and vegetables, and the results may help in the design of optimal preventive measures against Toxoplasma infection especially in female workers at reproductive age.